PENGARUH MODEL EXPERIENTAL LEARNING DALAM PEMBELAJARAN BAHASA INDONESIA TERHADAP KEMAMPUAN MENULIS TEKS LAPORAN OBSERVASI SISWA KELAS X SMA MUHAMMADIYAH SUKABUMI - Winahyu, Putri Taufik, Oktavia, Dara Rahma,Nazwa natasya,Widia; Winahyu, Dara Rahma; Taufik, Nazwa Natasya Putri; Oktavia, Widia (Jurnal Surya, 2025)
This study aims to determine the effect of the Experiential Learning model in Indonesian language learning on the writing skills of observational reports in tenth-grade students at Muhammadiyah Senior High School in Sukabumi. The background of this study stems from initial findings that students still experience difficulty in developing written ideas and often experience boredom when asked to write reports. This is related to the use of learning models that tend to be monotonous and lack direct experience for students. The Experiential Learning model was chosen because it provides opportunities for students to learn through real-life experiences, thereby strengthening their understanding and writing skills. The study used a descriptive qualitative approach with data collection through observation, interviews, and analysis of student writing. The results showed that the application of the Experiential Learning model improved students' learning focus, creativity, and ability to compose reports coherently and structurally. Furthermore, students became more enthusiastic and active during the learning process. Thus, the Experiential Learning model is effective as an alternative in teaching writing, particularly for observational reports.